(untitled) (Ibrahim Cardiac Medical Journal, 2019)
Background: To avoid harmful effect of cardiopulmonary bypass (CPB) used in off-pump coronary artery bypass graft (CABG) surgery, cardiac surgeons are now inclined to on-pump beating heart surgery (ONBEAT). However, the superiority of ONBEAT over Off-pump has not yet been conclusively established. This study compares the outcomes between off-pump and on pump beating heart CABG surgery. Methods: A total 249 consecutive patients who underwent non-emergency, primary isolated CABG from January 2014 to December 2017 by a single surgeon were included. The selected patients were assigned to either OPCAB group (Patients who received Off-pump beating heart CABG surgery, n=193) or to ONBEAT group (patients who received On-pump beating heart CABG surgery, n=56). The clinical outcomes were investigated and compared. Result: Forty percent of the patients were in their 5th decade of life. A male predominance was also observed. The two study groups were almost identical in terms of age and sex (p=0.983 and p=0.153 respectively). None of the conventional risk factors of ischemic heart disease (smoking, diabetes, hypertension and dyslipidaemia) were any different between the study groups (p > 0.05). Cerebrovascular disease, recent MI, congestive heart failure and left main disease were significantly higher in the on-pump beating heart group compared to those in the off-pump beating heart group (p < 0.05). The left ventricular ejection fraction (LVEF) was significantly lower in the former group than that in the latter group (p= 0.007). Both groups required 3 grafts on an average. Two patients in the on-pump group required Intra-Aortic Balloon Pump (IABP) support as opposed to none in the off-pump group (p=0.050). The mean cardiopulmonary bypass (CPB) time was 105.8 ± 46.5 in the on-pump group. Fourteen patients (25%) from off-pump group needed urgent switching to on-pump group. Postoperative drainage in the first 24 hours was significantly voluminous in the on-pump group (p < 0.001). The incidence of pneumonia, respiratory failure, arrhythmia, renal failure requiring haemodialysis and perioperative MI were significantly higher in the on-pump group (p < 0.001, p < 0.001, p=0.037, p < 0.001 and p=0.050 respectively). The patients with prolonged mechanical ventilation were also more in the on-pump group. The left ventricular ejection fraction (LVEF) was much lower and Intensive Care Unit (ICU) stay was longer in the on-pump group compared to those in the off-pump group (p < 0.001). The incidence of in-hospital mortality was also higher in the former group (p=0.037). Conclusion: OPCAB was associated with lower operative morbidity compared to ONBEAT cardiac surgery. However, the increased morbidity in ONBEAT group might have been influenced by a sizable proportion of patients from OPCAB group being switched to ONBEAT group due to their haemodynamic deterioration and frequent ventricular fibrillation. But on-pump CABG can be performed safely on high risk patients. Use of cardiopulmonary bypass and elimination of cardioplegic arrest may be beneficial to hemodynamically unstable patients. Ibrahim Card Med J 2017; 7 (1&2): 15-22